Thermodynamic test of Li2WO4 single crystals with low molybdenum doping: Enthalpy, interconnections, heat capacity. (February 2022) - Matskevich, N.I.; Shlegel, V.N.; Samoshkin, D.A.; Stankus, S.V.; Zaitsev, V.P.; Trifonov, V.A.
Highlights: Li2 W0.9875 Mo0.0125 O4 single crystal was grown by Czochralski technique first. No phase transitions were found for Li2 W1-0.025 Mo0.025 O4 (T = 320–997 K). Energy characteristics of Li2 W0.9875 Mo0.0125 O4 were studied by reaction calorimetry. Abstract: The thermodynamic test of Li2 WO4 single crystals doping by low molybdenum content with special emphasis on investigation of interconnections, enthalpy, heat capacity to improve device portfolio was performed. We reduced doping content in 7 times for Li2 W1-x Mox O4 in this investigation. The formation enthalpy of Li2 WO4 was estimated using interconnections. The heat capacity was measured for Li2 W1-0.025 Mo0.025 O4 single crystal ( T = 320–997 K) by differential scanning calorimetry. There were no phase transitions of Li2 W1-0.025 Mo0.025 O4 single crystal that made single crystals with low doping by molybdenum promising for application. The single crystal of lithium tungstate doped by 1.25% molybdenum (content was Li2 W0.9875 Mo0.0125 O4 ) was grown by LTG CZ for the first time. The reaction enthalpies of Li2 W0.9875 Mo0.0125 O4 single crystal were investigated by reaction calorimetry. The interconnections of formation enthalpies and lattice enthalpies of Li2 W1-x Mox O4 in the range (x = 1–0.0125) from x were established. It indicated the growth of phenakite structure in the range. It was shown that under conditions of low temperature gradients it was possible to grow perfect single crystals of lithium tungstate with low doping of molybdenum.